Is AI coming for your job? - Case, Antonia (New Philosopher, 2023)
The elastic figure that's bandied about is that some 50 per cent of jobs may disappear due to AI, but many more will be created, especially in fields such as data analytics, writing AI software, and AI consultancy (woo hoo…). "Don't bother getting a university degree", the 68-year-old man declares to the recent school leaver, "because AI is going to take all the jobs.